2009
DOI: 10.1038/emboj.2009.339
|View full text |Cite
|
Sign up to set email alerts
|

PKA phosphorylates and inactivates AMPKα to promote efficient lipolysis

Abstract: The mobilization of metabolic energy from adipocytes depends on a tightly regulated balance between hydrolysis and resynthesis of triacylglycerides (TAGs). Hydrolysis is stimulated by b-adrenergic signalling to PKA that mediates phosphorylation of lipolytic enzymes, including hormonesensitive lipase (HSL). TAG resynthesis is associated with high-energy consumption, which when inordinate, leads to increased AMPK activity that acts to restrain hydrolysis of TAGs by inhibiting PKA-mediated activation of HSL. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
183
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(200 citation statements)
references
References 49 publications
11
183
1
1
Order By: Relevance
“…As described in BAT (Qi et al 2008), AMPK is negatively regulated by cell-deathinducing like effector A (Cidea), inducing ubiquitination of the b subunit of AMPK and degradation of the enzyme. Also protein kinase A-mediated phosphorylation of a1-AMPK subunit at Ser-173 prevents activation of AMPK by LKB1-mediated phosphorylation of the a1-AMPK subunit at Thr-172, as found recently in white adipocytes (Djouder et al 2010).…”
Section: Role Of Ampk In Energy Metabolism and Glucose Homeostasissupporting
confidence: 65%
See 1 more Smart Citation
“…As described in BAT (Qi et al 2008), AMPK is negatively regulated by cell-deathinducing like effector A (Cidea), inducing ubiquitination of the b subunit of AMPK and degradation of the enzyme. Also protein kinase A-mediated phosphorylation of a1-AMPK subunit at Ser-173 prevents activation of AMPK by LKB1-mediated phosphorylation of the a1-AMPK subunit at Thr-172, as found recently in white adipocytes (Djouder et al 2010).…”
Section: Role Of Ampk In Energy Metabolism and Glucose Homeostasissupporting
confidence: 65%
“…It seems counter-intuitive (Daval et al 2006) that AMPK inhibits lipolysis, although it is itself activated in situations of increased lipolysis. It could be speculated (Djouder et al 2010;Sponarova et al 2005;Daval et al 2006;Gauthier et al 2008) that AMPK-induced reduction of lipolysis could be a feed back mechanism limiting the cellular energy drain, because part of the fatty acids released can be re-activated to acyl-CoA and re-esterified which requires ATP and generates AMP. Also, accumulation of large amounts of fatty acids could be deleterious for the cells.…”
Section: Ampk Function In Adipose Tissuementioning
confidence: 99%
“…Since inhibitor H89 or Rp-cAMP increased AMPK␣ subunit phosphorylation at Thr-172 along with a reduction in AMPK␣ subunit phosphorylation at Ser-485 (Fig. 1, b-d), and PKAmediated phosphorylation of AMPK␣ at Ser-485 negatively affects AMPK activity (10,(17)(18)(19), we examined whether blocking AMPK␣ subunit phosphorylation at Ser-485 would have an effect on glucose production in primary hepatocytes with constitutively activated PKA. Using adenoviral vectors needed to express similar amounts of the wild type (WT) and S485A mutant of AMPK␣1 proteins were used to primary hepatocytes isolated from floxed PKAR1a mice injected with Ad-CMV-Cre.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the hyperglucagonemia of diabetes can antagonize metformin efficacy by activating the cAMP-PKA pathway and cause metformin resistance. We and other investigators have found that the cAMP-PKA pathway negatively regulates AMPK activity through phosphorylation of the AMPK␣ subunit at Ser-485, which in turn reduces net phosphorylation at Thr-172 (10,(17)(18)(19). It is conceivable that the blockade of AMPK␣ phosphorylation at Ser-485 will augment AMPK activity and metformin efficacy.…”
mentioning
confidence: 99%
“…The weight loss could be attributed to abnormally increased lipolysis, due to the fact that PKA activation causes phosphorylation and consequent activation of hormone-stimulated lipase (HSL). 38 This was evident from the loss of subscapular and epididymal fat deposits, serum triglyceride levels and in the level of p-HSL in the adipose tissues of ROSA-CreER tg/tg ;Prkar1a fl/fl and ROSA-CreER tg/tg ;Prkar1a fl/fl ;BIM À / À mice injected with tamoxifen ( Figure 5). This lipolysis could occur irrespective of the Bim status.…”
Section: Discussionmentioning
confidence: 99%